Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Arrange the equations in the correct sequence to find the inverse of [tex]\( f(x)=y=\frac{3 x}{8+x} \)[/tex].

[tex]\[
\begin{array}{c}
1. \quad y = \frac{3x}{8+x} \\
2. \quad y(8+x) = 3x \\
3. \quad 8y + xy = 3x \\
4. \quad 8y = 3x - xy \\
5. \quad 8y = x(3 - y) \\
6. \quad x = \frac{8y}{3 - y} \\
7. \quad f^{-1}(x) = \frac{8x}{3 - x} \\
\end{array}
\][/tex]

[tex]\[
\begin{array}{c}
\quad \square \\
\downarrow \\
\quad \square \\
\downarrow \\
\quad \square \\
\downarrow \\
\quad \square \\
\downarrow \\
\quad \square \\
\downarrow \\
\quad \square \\
\downarrow \\
\quad \square \\
\end{array}
\][/tex]


Sagot :

To find the inverse of the function [tex]\( f(x) = y = \frac{3x}{8 + x} \)[/tex], we need to follow these steps. Here's the step-by-step solution with the equations arranged in their correct sequence:

1. Start with the function and express [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]:
[tex]\[ y = \frac{3x}{8 + x} \][/tex]

2. Rewrite the equation to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{3y}{8 + y} \][/tex]

3. Multiply both sides by [tex]\( 8 + y \)[/tex] to eliminate the fraction:
[tex]\[ x(8 + y) = 3y \][/tex]

4. Distribute [tex]\( x \)[/tex] on the left-hand side:
[tex]\[ 8x + xy = 3y \][/tex]

5. Get all terms involving [tex]\( y \)[/tex] on one side of the equation:
[tex]\[ 8x + xy - 3y = 0 \][/tex]

6. Factor out [tex]\( y \)[/tex]:
[tex]\[ 8x = 3y - xy \][/tex]

7. Combine terms with [tex]\( y \)[/tex]:
[tex]\[ 8x = y(3 - x) \][/tex]

8. Solve for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{8x}{3 - x} \][/tex]

Thus the inverse function is:
[tex]\[ f^{-1}(x) = \frac{8x}{3 - x} \][/tex]

The correct sequence of equations to find the inverse function is:

1. [tex]\( x = \frac{3y}{8 + y} \)[/tex]
2. [tex]\( x(8 + y) = 3y \)[/tex]
3. [tex]\( 8x + xy = 3y \)[/tex]
4. [tex]\( 8x = 3y - xy \)[/tex]
5. [tex]\( 8x = y(3 - x) \)[/tex]
6. [tex]\( y = f^{-1}(x) = \frac{8x}{3 - x} \)[/tex]

Arranged in this order, the equations correctly lead to the inverse function [tex]\( f^{-1}(x) = \frac{8x}{3 - x} \)[/tex].